Analisis Foot Spa Diabetic terhadap Sirkulasi Darah Perifer Kaki Pasien DM Tipe 1 dan 2 - Nur Anisah; Ricky Riyanto Iksan; Meria Woro Listyorini; Wiwie Herdalisa; Ratih Bayuningsih (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of diabetic foot spa on foot peripheral blood circulation in patients with type 1 and 2 DM. The method used was a pre-experimental study with a one-group pre-post test design. The population in this study were 32 respondents. Sampling technique with purposive sampling technique. The results showed that the statistical test paired t-test obtained a p value = 0.001 which means that diabetic foot spa is effective in improving the peripheral blood circulation of the feet in patients with type 1 and 2 DM. Health Center. Conclusion Diabetic foot spa is effective in improving the peripheral blood circulation of the feet. in type 1 and 2 DM patients. Keywords: Blood Circulation, Diabetes Mellitus, Diabetic Foot Spa,